Exploring The Symbiotic Economic Benefits Between Farmers and Herders to Promote Peaceful Coexistence in Taraba State Nigeria - Audu, Christina Tanko; Audu, Daniel Imoken-Asi (Advances in Social Sciences Research Journal, 2023)
This paper explored the symbiotic economic benefits between farmers and herders in Taraba State to promote peaceful coexistence. Taraba State is one of the states in the North East region of Nigeria that is mainly affected by the farmers-herders crisis. The paper illustrated the causes of the farmers-herders crisis which include the growing population, abandonment of the grazing reserve system, and proliferation of small arms and light weapons among others. Although the Federal and State Governments have responded in several ways, among which the creation of grazing reserves in 1965, the establishment of the National Commission for Nomadic Education (NCNE) in 1989, the use of the Armed Forces to curb internal security caused by farmers-herders crisis, proposed National Grazing Reserve Bill 2016, proposed Cattle Ranching System 2018, legislation prohibiting open grazing and the Great Green Wall Agency of the Federal Government. All these efforts by the Federal Government and various State Governments could not bring the desired peaceful coexistence between farmers and herders. The crisis still lingered in Taraba State and many other states. Therefore, the paper explored the symbiotic economic benefits that could be enjoyed by farmers and herders leading to peaceful coexistence. Some of the symbiotic economic benefits capable of stimulating peaceful coexistence are; after harvesting crops on their farm, they usually allow cattle to graze on the leftovers, during which excrement from the cows provide manure for the farm, use of yam and cassava peels for preparation of animal feeds, use of rice, guinea corn, maize, and millet chaff for animal feeds and use of animal waste as fertilizer. The author concluded that exploring the symbiotic economic benefits explicated in this paper can bring about peaceful coexistence between farmers and herders which will also result in a peaceful Taraba State. It was suggested that government and private individuals should establish ranches within farming communities in such a manner that herders can get animal feeds from farmers while the farmers get manure from the herders’ farms.